HHS PERSONNEL INSTRUCTION ON WORKPLACE SMOKING POLICY: GUIDANCE ON PERSONNEL ISSUES (Tufts Archival Research Center, 2007)
Copy; Missing Attachments; Memo to HHS Heads of Operating and Staff Divisions and Regional Directors from Thomas McFee, Assistant Secretary for Personnel Administration giving guidance on personnel issues relating to establishment of smoke-free environment in HHS building space. Indicates that unions have been consulted and reviewed the policy. Identifies reasons for ban, primarily health-based for both nonsmokers and smokers. Asserts that resources are available for addiction counseling, training, and education, but not for medical care, treatment, or rehabilitation.